The Effect of Soft Skills, Hard Skills, and Self-Efficacy on Work Readiness with Part-Time Work Experience as a Mediation Variable - Aura Eri Ratna Mahesti; Jati Waskito (Universitas KH. Abdul Chalim Mojokerto, 2026)
This study examines the effects of soft skills, hard skills, and self-efficacy on work readiness, with part-time work experience as a mediating variable among Generation Z in the Solo Raya region. The conceptual framework is based on Social Cognitive Career Theory (SCCT), which highlights the interaction between personal factors, learning experiences, and career-related outcomes. A quantitative approach was employed using primary data collected through an online questionnaire from Generation Z individuals aged 17–28 who had part-time work experience, selected using purposive sampling. Five constructs were measured on a 5-point Likert scale: soft skills, hard skills, self-efficacy, part-time work experience, and work readiness. Data were analyzed using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS 4. The results show that soft skills have a positive and significant direct effect on work readiness, while hard skills and self-efficacy do not have a direct influence. However, all three variables significantly affect part-time work experience, which in turn positively influences work readiness. Furthermore, part-time work experience mediates the relationship between hard skills and work readiness, indicating that technical competencies contribute to readiness primarily through experiential learning. These findings reinforce the relevance of SCCT and emphasize the importance of practical work experience in enhancing Generation Z’s work readiness.